Sri Lanka's peace process--2002 : critical perspectives - Uyangoda, Jayadeva; Uyangoda, Jayadeva; Perera, Morina; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 2003)
Contributed articles.
Keywords: Tamil (Indic people) -- Sri Lanka -- Politics and government; Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Ethnic relations